Cashing out, cashing in: rural change on the south coast of Western Australia - Curry, George; Koczberski, Gina (Routledge, 2001)
Over the past century the cultural and physical landscape of the Shire of Denmark on the south coast of Western Australia has been transformed by successive waves of in-migrants. The paper examines the period since the early 1970s when alternative lifestylers and early retirees, attracted by the district's natural beauty and low land prices, began moving in and acquiring former Group Settlement holdings. The activities of these and subsequent 'alternatives' and 'cashed out' early retirees settling in the district have raised the marketability of the Shire's cultural capital. These changes have occurred in association with broader processes of rural restructuring and changing notions of 'rurality'. Increasingly, Denmark's cultural and physical landscape has become a highly marketable product for consumption by Perth's affluent middle classes. In recent years land prices have risen rapidly as speculators and financiers seek to 'cash in' on the 'cashed out' society. The paper explores these issues and relates them to broader processes of economic and social change occurring at the national and international